Double-bundle anterior cruciate ligament reconstruction in patients aged 60 years and older - Kentaro Miyamoto; Kazutoshi Kurokouchi; Shinya Ishizuka; Shigeo Takahashi; Takashi Tsukahara; Ryosuke Kawai; Tadahiro Sakai; Hiroki Oba; Takefumi Sakaguchi; Shiro Imagama (Elsevier, 2024)
Background: This study aimed to examine the clinical outcomes of double-bundle (DB) anterior cruciate ligament (ACL) reconstruction in patients aged ≥60 years. Methods: Anatomical DB-ACL reconstruction using hamstring tendon autografts was performed in 13 patients aged ≥60 years at our institution between June 2012 and May 2018. The patients included seven men and six women, and the mean age at surgery was 65.0 years (range, 60-73 years). The mean time from injury to surgery was 80.5 months (range, 1-480 months), and the mean follow-up time was 26.2 months (range, 24-42 months). All patients were assessed based on physical examination findings, clinical scores, Kellgren-Lawrence grades preoperatively and at the final postoperative follow-up, intraoperative meniscal or chondral lesions, and perioperative complications. Status of returning to sports for all patients was assessed at the final follow-up. Results: The mean side-to-side differences by arthrometer improved from 4.3 mm (range, 2-8 mm) to 0.9 mm (range, 0-2 mm), and the positive pivot-shift test decreased from 100% to 8%. The mean extensor muscle strength was 93.3% (range, 74-116%) postoperatively. The mean Lysholm score improved from 71.1 (range, 27-85) to 95.2 (range, 89-100). Ten of the 13 patients (77%) returned to their pre-injury level of sports performance, and one patient (8%) returned to sports with less intensity. Intraoperatively, meniscal tears were observed in 10 patients (77%), and chondral lesions >grade 2 were observed in 11 (85%). One patient developed perioperative complications. At the final follow-up, the Kellgren-Lawrence grade worsened in only one patient. No re-injury or infection was observed, and revision surgery was not required for any patients. Conclusions: Anatomical DB-ACL reconstruction could provide satisfactory clinical outcomes and knee function restoration in patients aged ≥60 years. Level of evidence: A retrospective study, case series (IV).